Regimes de bem-estar social na América Latina : uma discussão conceitual e uma meta-análise dos estudos comparativos - Pedro Mendes Rufino Barbosa (2015)
The welfare regimes approach, formulated by Esping-Andersen (1991), provides an analytical advance in welfare states studies. Specially, he emphasized the variation of social rights scope among OECD countries. More recently, such approach has been used to interpret the Latin America context through comparative analysis. Therefore, this work seeks to analyse that literature debating the applicability to Latin America of both welfare regime concept and theoretical assumptions about europeans cases. Finally, we will make an meta-analysis based on empirical studies, in order to identify contradictions and confirmations among of Latin America countries classifications.